FAKTOR YANG BERHUBUNGAN DENGAN KEAKTIFAN KADER DALAM KEGIATAN POSYANDU DI WILAYAH PUSKESMAS KENARILANG KABUPATEN ALOR - Pering, Elisabeth Eka; Takaeb, Afrona E.L; Riwu, Rut Rosina (Pusat riset dan Inovasi Nasional, 2022)
The activity of cadres is very important in posyandu activities because if the cadres are not active, the provision of health services and posyandu activity programs cannot run properly. The purpose of this study was to determine the factors related to the activeness of cadres in posyandu activities in the working area of ​​the Kenarilang Health Center, Alor Regency. This type of quantitative research uses a cross sectional study approach. The study population consisted of 210 cadres, with a total sample of 68 cadres using convenience sampling/accidental sampling. Data were analyzed using chi-square statistical test. The results showed that the variables of knowledge (ρ = 0.023), occupation (ρ = 0.022), incentives (ρ = 0.002), and support from community leaders (ρ = 0.043) had a relationship with the activeness of cadres in posyandu activities. Meanwhile, the attitude variable (ρ=0.492) had no relationship with the activeness of cadres in posyandu activities. Puskesmas Kenarilang should improve training on promotive efforts when providing cadres in increasing knowledge about the duties and functions of posyandu. Village and sub-district governments should always provide appropriate incentives as motivation in increasing the activity of cadres in posyandu activities, and it is hoped that community involvement will always support cadres in posyandu activities.